Decoupled recovery of energy and momentum with correction of n = 2 error fields. (6th July 2015) - Paz-Soldan, C.; Logan, N.C.; Lanctot, M.J.; Hanson, J.M.; King, J.D.; La Haye, R.J.; Nazikian, R.; Park, J.-K.; Strait, E.J.
Abstract: Experiments applying known n   =  2 'proxy' error fields (EFs) find that the rotation braking introduced by the proxy EF cannot be completely alleviated through optimal n   =  2 correction with poorly matched poloidal spectra. This imperfect performance recovery demonstrates the importance of correcting multiple components of the n   =  2 field spectrum and is in contrast to previous results with n   =  1 EFs despite a similar execution. Measured optimal n   =  2 proxy EF correction currents are consistent with those required to null dominant mode coupling to the resonant surfaces and minimize the neoclassical toroidal viscosity (NTV) torque, calculated using ideal MHD plasma response computation. Unlike rotation braking, density pumpout can be fully corrected despite poorly matched spectra, indicating density pumpout is driven only by a single component proportional to the resonant coupling. Through precise n   =  2 spectral control density pumpout and rotation braking can thus be decoupled. Rotation braking with n   =  2 fields is also found to be proportional to the level of co-current toroidal rotation, consistent with NTV theory. Plasmas with modest counter-current rotation are insensitive to the n   =  2 field with neither rotation braking nor density pumpout observed.